Parathyromatosis following spontaneous rupture of a parathyroid adenoma: natural history and the challenge of management. Issue 7 (11th July 2013) - Sim, I.‐W.; Farrell, S.; Grodski, S.; Jung, C.; Ng, K. W.
Abstract Parathyromatosis, the presence of small nodules of hyper‐functioning parathyroid tissue scattered throughout the soft tissues of the neck and superior mediastinum, is a rare cause of persistent primary hyperparathyroidism. We report the first case of parathyromatosis secondary to spontaneous rupture of a parathyroid adenoma. Despite running an indolent course, this case highlights the potential challenges of management of parathyromatosis and the value of calcimimetic therapy as an adjunct to surgery for disease control.